2017
DOI: 10.1039/c7ra11031f
|View full text |Cite
|
Sign up to set email alerts
|

Potential waste from palm empty fruit bunches and eggshells as a heterogeneous catalyst for biodiesel production

Abstract: Biodiesel is one of the potential alternative energies produced from a variety of vegetable oils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…The surface area of silica obtained in this study was also comparable to that reported in the literature; by Faramawy et al (2016), with a surface area of 12-67 m 2 g -1 , and Putra et al (2017), who produced silica catalyst with a surface area of 39.7 m 2 g -1 . Figure 4 shows the results of the SEM characterization for the alumina and silica catalysts.…”
Section: Characterization Results Of the Extracted Alumina And Silicasupporting
confidence: 88%
“…The surface area of silica obtained in this study was also comparable to that reported in the literature; by Faramawy et al (2016), with a surface area of 12-67 m 2 g -1 , and Putra et al (2017), who produced silica catalyst with a surface area of 39.7 m 2 g -1 . Figure 4 shows the results of the SEM characterization for the alumina and silica catalysts.…”
Section: Characterization Results Of the Extracted Alumina And Silicasupporting
confidence: 88%
“…Various homogenous acids/base catalysts such as CH 3 NaO, H 2 SO 4 , HCl, NaOH, and KOH were used for the biodiesel production. These catalysts have virtuous catalytic performance but have several drawbacks on commercialization because of saponification, nonreusability, and less reactivity to high free fatty oils . Mainly, an acid pretreatment process is a prerequisite for the homogenous base catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…These catalysts have virtuous catalytic performance but have several drawbacks on commercialization because of saponification, nonreusability, and less reactivity to high free fatty oils. 13,14 Mainly, an acid pretreatment process is a prerequisite for the homogenous base catalyst. This pretreatment exhibits high cost of biodiesel production, high energy consumption, and corrosion in the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, Ansori et al 195 197 CaO/Zn, 198 CaO/KF/Fe3O4, 199 CaO/SiO2 based on palm empty fruit bunch (PEFB), 200 and Mo-Zr/CaO 201 etc.…”
Section: Biomass-based Catalystmentioning
confidence: 99%